HEALTH INSURANCE FOR WORKERS IN PANDEMIC TIME - Devi, Syahrindra (Faculty of Law, Khairun University, 2022)
The current Covid-19 (Coronavirus Disease-19) pandemic has become a challenge and also a new problem. The pandemic that has been going on for more than a year has had a significant impact on many lines of human life. The purpose of this paper is to find out the efforts made by the government in order to ensure the health of workers during a pandemic. This study uses a normative juridical approach, because it uses secondary data as the main data. Data collection was carried out through a literature study, which is a data collection technique that was carried out through a literature study as literature which can provide a theoretical basis relevant to the issues to be discussed. Based on data reported by the Ministry of Manpower, there are 2.8 million workers directly affected by Covid-19. They consist of 1.7 million formal workers laid off and 749.4 thousand laid off (Labor). However, it was unlucky for the company to terminate the employment relationship, arguing that it was